Improving the skills of the residents of the Abadi Megah Regency Jombang in microgreens cultivation techniques as an effort to improve family food security - Dyah Ayu Sri Hartanti; Yessita Puspaningrum; Anggi Indah Yuliana (Universitas Muhammadiyah Magelang, 2022)
Family food security is the main support for the sustainability of human life, especially during the Covid-19 pandemic. Increasing access to nutritious food sources for families can be pursued by implementing microgreens cultivation at the household scale. The objectives of this training are to improve the skills of the residents regarding the use of used bottles as a medium for growing microgreens and microgreens cultivation techniques. The method used is a community empowerment method consisting of demonstrations and training. Evaluation of the training showed that the understanding of residents'of the Abadi Megah Regency, Jombang on how to use used plastic bottles increased from 23% to 95% and there was an increase in the skills of residents in processing used plastic bottles as microgreens planting media from 24% to 94%. In addition, this training not only increased residents' understanding of how to cultivate microgreens from 17% to 95% but also increased the skills of residents in microgreens cultivation from 2% to 69%.